Gute Nachbarschaft - Serra, Pedro (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
This essay focuses on A Cidade e as Serras (1901), a semi-posthumous novel by Eça de Queirós. The argument holds that the philological legacy configures a tropology that allows the evaluation of its genologic aspirations, in the aftermath of Ega's strong investment in the naturalistic model. The sintagms «friendship», «book» or «library» under consideration (and that compel us to answer them) form a company of ghosts that temporalize (anachronize) the reading of the novel, or the novel as the product of that reading. In the end of the century those allegorical operators dessubstantiate the Reality as «strong» objectal Origin —onthologically stable—, an Origin made symbol, in the development of the 19th century, precisely by the philological cience(s), agent of all naturalizations. In A Cidade e as Serras the philological company of ghosts autonomize the novel and assumes the losses of that agency: its own cadaverization.
Keywords: José Maria Eça de Queirós; La ciudad y las sierras